Characteristics and outcome of therapy‐related myeloid neoplasms: Report from the Italian network on secondary leukemias. Issue 5 (3rd March 2015) - Fianchi, Luana; Pagano, Livio; Piciocchi, Alfonso; Candoni, Anna; Gaidano, Gianluca; Breccia, Massimo; Criscuolo, Marianna; Specchia, Giorgina; Maria Pogliani, Enrico; Maurillo, Luca; Aloe‐Spiriti, Maria Antonietta; Mecucci, Cristina; et al.
<x xml:space="preserve">Abstract</x> Therapy‐related myeloid neoplasms (t‐MN) are a complication of cytotoxic treatment for primary tumors and autoimmune diseases. We report data on 277 t‐MN patients, recruited between 1999 and 2013 by the Italian Network on Secondary Leukemias (104 retrospectively and 173 prospectively registered). Median age at t‐MN diagnosis was 64 years (range, 21–87). Most frequent primary malignancies (PMs) were lymphoproliferative diseases and breast cancer. One hundred and thirty‐three patients had received chemotherapy (CHT), 43 patients radiotherapy (RT), and 101 patients combined CHT/RT for PM. Median time between cytotoxic treatment and t‐MN was 5.7 years, with t‐MN following RT alone associated with significantly longer latency, compared to CHT or combined CHT/RT (mean, 11.2 vs. 7.1 years, P = 0.0005). The addition of topoisomerase‐II inhibitors to alkylating agents was associated with shorter latency compared to alkylating agents alone (median, 6 vs. 8.4 years, P = 0.02). Median survival was 14.6 months from t‐MN diagnosis, and was significantly longer in patients treated with allogeneic stem cell transplantation. Significant factors for survival at the multivariable analysis included age, adverse karyotype, and degree of anemia. Our data underline the prognostic importance of karyotype and age in t‐MN, similar to de novo acute myeloid leukemia. Treatment approaches should not preclude the use of conventional treatments for younger t‐MN patients, including allogeneic stem cell transplantation as potentially curative approach. Am. J. Hematol. 90:E80–E85, 2015. © 2015 Wiley Periodicals, Inc.